Aplikasi 3D Interaktif Walkthrough Gedung Fakultas Ilmu Komputer Universitas Widya Dharma - Aryati Wuryandari; Hendro Joko Prasetyo; Edi Nur Handono (Universitas Muhammadiyah Purworejo, 2018)
Presentation of information in improving services needs to be considered by the Faculty of Computer Science (Fasilkom) Widya Dharma University (Unwidha) Klaten to be able to main-tain and improve its applicants. Presentation of Information in the form of a 3D walkthrough is used to better introduce and promote Fasilkom to the public. Application development method uses multimedia development life cycle. 3D visualization of buildings and information about Fasilkom's facilities interactively is expected to help related parties to get to know Fasilkom and at the same time provide additional value for Fasilkom and UNWIDHA.